Kasus Bupati Garut dan Fenomena Ahmad Fathanah: Pembelajaran Komunikasi Keluarga - Yunus, Ulani (Bina Nusantara University, 2013)
Mass media reports about two males figure who have the power and wealth associated with the case in love relationship. It is not only seen as an ?accident